Comparison of the efficacy and safety of drug therapies for macular edema secondary to central retinal vein occlusion. Issue 12 (28th December 2018) - Qian, Tianwei; Zhao, Mengya; Wan, Yongjing; Li, MengXiao; Xu, Xun
Abstract : Objectives: To evaluate the efficacy and safety of anti-vascular endothelial growth factor (VEGF) agents and corticosteroids for the treatment of macular oedema (ME) secondary to central retinal vein occlusion (CRVO). Design: Systematic review and network meta-analysis. Participants: Patients from previously reported randomised controlled trials (RCTs) comparing anti-VEGF and corticosteroids for the treatment of ME secondary to CRVO. Methods: Literature searches were conducted using PubMed, Medline, Embase, Cochrane Library and clinicaltrials.gov until March 2017. Therapeutic effects were estimated using the proportions of patients gaining/losing ≥15 letters, best-corrected visual acuity (BCVA) and central retinal thickness (CRT). Treatment safety was estimated using the proportions of adverse events, namely increased intraocular pressure (IOP), cataracts, vitreous haemorrhage (VH) and retinal tear. The software ADDIS (V.1.16.8) was used for analysis. Treatment effect and safety of different drugs could be ranked based on simulation. Results: Eleven RCTs comprising 2060 patients were identified. Regarding patients gaining ≥15 letters, aflibercept and ranibizumab were significantly more effective than sham/placebo at 6 months. Regarding patients losing ≥15 letters at 6 months, ranibizumab showed significant improvement compared with dexamethasone. Aflibercept, bevacizumab or ranibizumab showed greater improvements in BCVA than sham/placebo at 6 months. Intravitreal ranibizumab injection demonstrated greater CRT reduction than both sham and dexamethasone did. Dexamethasone had a higher risk of increased IOP than aflibercept and ranibizumab. Ranibizumab demonstrated a greater risk of cataracts than dexamethasone. Aflibercept and ranibizumab demonstrated low incidence of VH and retinal tear, respectively. Aflibercept had a slight advantage over ranibizumab as assessed by benefit–risk analysis. Conclusions: Anti-VEGF agents have advantages in the treatment of ME secondary to CRVO. Aflibercept and ranibizumab showed marked BCVA improvement and CRT reduction. Aflibercept may have a slight advantage over ranibizumab. The results of this study can serve as a reference for clinicians to provide patient-tailored treatment. PROSPERO registration number: CRD42017064076.